Game Analysis between Government and Coal Mine Enterprise in Coal Resource Exploitation Environmental Impact Compensation - MENG Zhao-jian (Institute of Advanced Engineering and Science, 2013)
From the angle of compensation subject and compensation object, the interest involved with stakeholder was analyzed. Based on game theory, the relation between government and coal mine enterprise was analyzed. Through the research, the government should constraint the coal mine enterprise behavior, set up coal resources development environmental impact compensation incentive mechanism, increase coal resources exploitation and environmental compensation violations punishment, and incentive the coal mining enterprises. DOI: http://dx.doi.org/10.11591/telkomnika.v11i8.3128